Referral of Research Participants for Ancillary Care in Community-Based Public Health Intervention Research: A Guiding Framework. (27th September 2015) - Merritt, Maria W.; Katz, Joanne; Mojtabai, Ramin; West, Keith P.
Abstract: Researchers conducting large community-based studies among underserved populations may collect data on health conditions that are little-acknowledged in the local setting, and for which there are few if any services for referral of participants who need follow-up diagnosis and care. In the design and planning of studies for such settings, investigators and research ethics committees may struggle to determine what constitutes effective referral and whether it is reasonably available. We offer a guiding framework for referral planning, informed by our experiences of research in the field and of service on research ethics committees, to support evaluation of local referral resources and consideration of the benefits, burdens and risks of referral in the local setting. The framework addresses both the impact of referral on the well-being of the people who would be referred and the impact that referral of study participants would have on local people outside the study. We use a sustained discussion of three field-based case examples to illustrate the ethical concerns at issue and to demonstrate the use of the referral planning framework.